Examining the Synergy between Islamic Values and 21st Century Competencies in Islamic Religious Education: A Mixed-Methods Study - Ramadhoni, Muhammad Abdul; Ali, Moh (Research Horizon, 2026)
The integration of Islamic ethics with 21st-century competencies is essential to strengthen the relevance of Islamic religious education in responding to contemporary educational challenges. This study aims to describe the implementation of Islamic ethics and 4C competencies integration in PAI learning. A mixed-methods sequential explanatory design was employed. Quantitative data were collected through a four-point Likert-scale questionnaire administered to 24 students to measure five integrated indicators, namely, critical thinking based on Islamic justice, creativity with value (maslahah), trustworthy collaboration, civilized communication, and ethical decision making, as well as student learning engagement. Qualitative data were obtained through semi-structured interviews, classroom observations, and document analysis involving PAI teachers and selected students. The findings indicate high achievement in trustworthy collaboration and civilized communication, along with a strong linkage between analytical skills and moral principles in critical thinking and ethical decision-making. Creativity with value and affective engagement were relatively lower, suggesting limited innovation and learning variation. The integration of Islamic ethics and 21st-century competencies enhances students’ cognitive, affective, and social development. This study implies the need for project-based learning, interactive media, and broader school–community collaboration to strengthen meaningful and contextual PAI learning.